Future groundwater extraction scenarios based on COMSOL multiphysics for the confined aquifer at Linfen basin, Shanxi Province, China. Issue 1 (1st January 2017) - Liu, Lin; Liu, Xuemei
Abstract: As one of the six largest river basins in Shanxi Province, China, Linfen basin has been in severe groundwater level declining status caused by over-extraction of groundwater since 1976, along with dense distribution of land subsidence and ground fissures. Future Groundwater drawdown analysis due to over-extraction is a major concern for not only water resource management, but also preventive and controlling measures of land subsidence and ground fissures. Consequently, in this paper groundwater extraction dynamic process for the confined aquifer at Linfen basin was simulated based on COMSOL Multiphysics. Then future groundwater extraction scenarios, namely, groundwater drawdown values within a period of consecutive 20 years and their consequent impacts on confined aquifer discharge amount to the Yellow River were predicted. The results demonstrated that the groundwater drawdown value and lateral discharge to the Yellow River would reach 7.07 m/a and 0.56 × 10 8 m 3 /a respectively in 10 years, while these two numbers drop to 3.44 m/a and 0.25 × 10 8 m 3 /a in 20 years. In order to provide valuable information for local government and policy makers, the paper would finally quantify a sustainable groundwater extraction value—20% of current groundwater extraction amount.